Analysis of Application of Waqf Accounting Based on PSAK 112 at the Wihdatul Ummah Batusangkar Foundation - Erfi Khairani; Ilham Illahi (Doktoral Ilmu Manajemen, Universitas Pasundan, 2023)
This research is motivatediby the financial reports prepared by the Wihdatul Ummah Foundation where there is a difference in the recording made by Nazir with PSAK 112 where there is no separation of waqf assets and the lack of maximum financial reporting in 2022. This studyiaims to understand in depth how the application of waqf accounting carried out by the nadzhir waqf of the Wihdatul Ummah Batusangkar Foundation is in accordance with PSAK 112. The type of research that the authors conducted was (field research) fieldiresearch with a qualitative approach, namelyiconducting in-depth analysis of the problems found in the field. The results of this study indicate that the recognition and measurement carried out are in accordance with PSAKi112. Nazir waqaf Qurratta Ayyun Batusangkar has not been optimal in managing and presenting financial statements based on PSAK 112.